Use of chelator and antioxidant in experimental lead toxicity: Effect on immune system - PATRA, R C; SWARUP, D; SINGH, D K (The Indian Journal of Animal Sciences, 2013)
Crossbred calves (20) aged I month, were randomly divided into groups A (5) and B (15). Calves of group B were given oral administration of lead (Pb)@ 7.5 mg oflead acetate/kg body weight for 28 days to study its effect on humoral and cell-mediated immune response following challenge with killed Brucella abortus cells on day 10 after cessation of lead exposure and treatment with EDTA and EDTA plus a tocopherol. Pb-exposed calves of group B were further subdivided in 3 groups (B1, 82 and B3) The animals of group BI were not given any treatment and served as exposed untreated control. It was concluded that exposure to lead markedly reduced the production of antibody which was further potentiated by treatment with Ca-EDTA alone (B,) or in combination with a tocopherol (B3). Increase in skin fold thickness following intrademlal injection of 100 mg of son icated cens on day 21 following sensitization of animals was greater in animals exposed to lead and still more in Pb exposed Ca-EDTA treated calves compared to control animals, indicating augmentation of cell-mediated immune response in lead toxicity.